Perlindungan Hukum Terhadap Korban Tindak Pidana Pornografi (Studi Putusan Nomor 14/Pid.B/2024/PN Sdr) - Adityah Anugrah Tanur; Muhammad Sabir Rahman; Lia Trizza F A; Kairuddin Karim; Muh. Fadli Faisal R (Judge : Jurnal Hukum, 2025)
This article focuses on a normative legal study regarding the application of the Pornography Law, specifically examining Decision Number 14/Pid.B/2024/PN Sdr issued by a court in Sidenreng Rappang Regency. This study uses a legislative and analytical approach to review the legal considerations used by the judge. The legal material sources used include primary and secondary legal materials, which are then analyzed qualitatively and prescriptively. The results of the analysis indicate that the Panel of Judges in the decision legall y and convincingly declared the defendant guilty of the crime of pornography, in accordance with the provisions of Article 35 in conjunction with Article 9 of the Republic of Indonesia Law Number 44 of 2008 concerning Pornography. The judge's decision was based on legal considerations (such as witness statements, evidence, and prosecutor's demands) as well as non - legal considerations (including the impact of the act, aggravating factors, and mitigating factors). This court decision is considered appropriate because it is consistent with applicable laws and regulations. As a result, the defendant was sentenced to 5 years' imprisonment, plus the obligation to pay court costs of Rp5,000.00 (Five Thousand Rupiah)